Planned stage endovascular treatment for complex wide neck aneurysm - Ahmad Sobri M,; Spelle L,; Moret J, (Department of Surgery, UKM Medical Centre, 2011)
Treatment of a complex, wide neck aneurysm sometimes cannot be achieved in a single endovascular session. This case illustrates a planned stage endovascular treatment of a complex aneurysm with remodeling technique aiming to eliminate risk of rebleeding during acute phase in the first stage of treatment, and complete occlusion in the second stage of treatment. After first stage, separation between coil mass and neck remnant was clearly shown indicating presence of neointimal layer. Multiple sessions also provide proper planning and more controlled treatment of difficult aneurysms.